2022
DOI: 10.5614/j.eng.technol.sci.2022.54.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Soundscape Composition to Identify the Ideal Soundscape for Various Activities

Abstract: Soundscapes are affected by several factors and one of them is the activities done in the space concerned. People expect different acoustic environments for different activities, but there is no specific guidance for designing an ideal acoustic environment for different activities. This study aimed to identify ideal urban acoustic environments for four different activities: reading, relaxing, talking with friends, and playing with children. The ideal acoustic environment was evaluated using the soundscape comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The audio editing processes involved in creating the soundscape composition aimed to produce creative listening experiences, as is often the intention in soundscape composition (Sarwono et al 2022;Truax 2002;Westerkamp 1999). In this case, the soundscape compositions form a reflective repository to identify particular sounds or sonic activities.…”
Section: An Overview Of the Sounding Covid-19 Repositorymentioning
confidence: 99%
“…The audio editing processes involved in creating the soundscape composition aimed to produce creative listening experiences, as is often the intention in soundscape composition (Sarwono et al 2022;Truax 2002;Westerkamp 1999). In this case, the soundscape compositions form a reflective repository to identify particular sounds or sonic activities.…”
Section: An Overview Of the Sounding Covid-19 Repositorymentioning
confidence: 99%
“…There are also studies focusing on the effects of anthropological (Lepore et al, 2016). Sarwono et al (2022) also found that talking with friends and playing with children are positively associated with anthropological sounds (i.e., people talking, footsteps, and slow music), while relaxing and reading activities are more likely to occur when the environments are rich in natural sound (i.e., water, wind, birds chirping, and rain).…”
Section: Exploring the Benefits Of Nature Through Human Perceptions A...mentioning
confidence: 99%
“…Urban settings dominated by natural features, such as city parks, pocket parks, gardens, and landscape boulevards were often mentioned as favorite places. Engagement with the soundscape in urban areas is also affected by the activity done ( Sarwono et al, 2022 ) and vice versa, though scant evidence has emerged in soundscape research clarifying its relationship with activity type. The sound pressure level is one of the most important factors affecting choice of activity when it exceeds a certain range ( Nilsson et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%